Evaluation the usability of the da'wah management study program website using the heuristic evaluation method - Rahmayani, Mentari Tri Indah; Mahsuri, Mahsuri (Institute of Computer Science (IOCS), 2024)
The Da'wah Management Study Program is one of the study programs at STAIN Bengkalis which has used the website as a place to Get information and promotional media for the Bengkalis Stain Da'wah Management Study Program. The function of this website is to make it easier for users to access information relating to institutions and the Da'wah Management Study Program. In implementing this website there are still several problems, namely: information that is not updated enough, an unattractive appearance, a lack of visitors and a website that often has errors. The aim of this research is to analyze, evaluate and measure the level of user satisfaction of the missionary management study program website using the heuristic method evaluation and to provide recommendations to the website manager of the da'wah management study program so that it can be used as a solution for increasing user satisfaction based on the success rate of the website. Data collection through observation, interviews, and questionnaires. The sampling technique uses the Slovin and Simple Random techniques Sampling. Based on research results on data obtained is that the percentage value of Usability is obtained Total testing was found to get a score of 36%, which means it shows that the website is good enough for you users, for a total not found, got a score of 32%, which means it shows that the website not good for the user.